Nutritional and toxicological analysis of phoenix dactylifera (date palm) powder used as a drink (Bangladesh Journal of Medical Science, 2018)
Objective: Phoenix dactylifera fruit widely used in Muslim countries.They have religious attachment to it and also it had many health benefits. It is essential to investigate nutritional values of Phoenix dactylifera fruit in dried powder form and to find out any toxicological changes during processing of this dried powder drink.Method: Dried date powder was prepared from fresh fruit by drying it and its nutritional value and toxicological studies were carried out. The acute oral toxicity study of date powder was conducted on wistar strain rats by oral route in a dose of 0.5g/kg body weight and 0.1g/kg body weight.Result: The results of biochemical analysis of dehydrated date powder exhibited that it possesses high energy value of 311 Kcal, carbohydrate 70.5%, dietary fiber 7.3%, fat content 2.1%, protein 2.6%, and mineral content 2.2%. Whereas, total sugar was found to be as 63.2% and moisture content 2.3%. The test drink showed no sign of toxicity or death during the whole observation period (fourteen days) in rats. No group of animal showed any unusual change in behavior or in locomotors activity. The macroscopic studies of vital organs i.e. heart, liver, spleen, lungs and kidneys exhibited that they were normal.Conclusion: As a result of these studies it can be concluded that from processing of fresh fruit to dried powder along with its nutritional and toxicological studies no hazardous material like toxins were produced. So it can be used safely.Bangladesh Journal of Medical Science Vol.17(2) 2018 p.263-269